Analysis of Width, Height and Width/Height Ratio of Crowns of Maxillary Anterior Teeth - Bakhtawar Saleem, Arslan Mahmood, Aamir Mehmood Butt, Naheed Najmi, Shuja Aslam, Syed Mahmood Shah, Salman Shams (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The vital role of the prosthetic dentistry is not only the restoration of function, comfort and health of oral tissues but also esthetics in general. Upper jaw anteriors commonly seen in smile and contribute to the beauty of a smile. This study may help us to determine standard ideal tooth dimension of maxillary anterior six teeth to restore pleasing esthetics. Aim: To determine the mean width, height and width/height ratio of clinical crowns of natural maxillary anterior six teeth. Setting: Department of Prosthodontics, dental OPD LUMHS Jamshoro. Duration: Six months from 2018 to 2019 Design: Cross-sectional descriptive. Methods: A total of 101 Volunteer subjects with maxillary anterior six teeth present in mouth were included in the study. Impression of maxillary arch was made. The maximum mesiodistal width perpendicular to the longitudinal axis of the tooth and maximum cervicoincisal (CI) length parallel to the longitudinal axis of the maxillary central incisors, lateral incisors, and canines were recorded and width/height ratio was calculated. The final measurements were recorded into proforma. Results: The average age of the subjects was 24.74±3.89 years. The average crown width / length ratio was 0.78±0.12mm for right central incisor and 0.78±0.12mm left central incisor. The average crown W/H ratio was 0.63±0.16mm for right lateral incisor and 0.63±0.14mm left central incisor. Similar the mean crown W/H ratio was 0.64±0.16mm right canines and 0.65±0.18mm left canine. Conclusion: The tooth dimension showed high precision in length/width ratio. Since it showed the least variance in both genders, the crown width-to-length ratio was recognized as the most reliable standard.